Contextualisation of optico-plastic: The effects of Alexander Archipenko and Ljubomir Micić's cooperation - Latifić Amra (Akademija umetnosti Univerziteta u Novom Sadu, 2021)
One of the most important representatives of our culture in the 1920's is Ljubomir Micić, who connects a wide range of activities. His activity as the editor and founder of Zenit, poet, writer, critic, theorist, collector and organiser of exhibitions, attracted the attention of the world's avant-garde. Micić's project entitled Archipenko - the New Plastic, an album-monograph, appeared in Belgrade in 1923. The monograph had a print-run of 100 copies; it includes Archipenko's artistic opus until 1923 and represents one of the world's earliest, according to Zoran Markuš perhaps even the oldest monograph about sculptor Alexander Archipenko. An additional feature of this monograph is the cooperation between the writer and the world artist, because Archipenko himself participated in the preparation of this publication; he was the one to choose reproductions - 13 sculptures and 2 drawings. On this occasion, Micić wrote the introductory text, and according to Irina Subotić, it is a "manifesto of zenithist sculpture, seen through the optics of this sculptor's oeuvre". The introductory text is entitled Towards Optico-plastic, and Micić writes it in Belgrade on the 20th September. Here he introduces a new theoretical concept of optico-plastic, and in a specific literary way argues that Archipenko's art is one step towards optico-plastic, as he significantly defines a new style of absolute plasticity. Micić combines oculocentric aesthetics and optical illusionism dimension in the new concept, anticipating the third dimension which only eye can perceive. It is clear that Micić possessed the ability to anticipate, not only new concepts in the domain of theoretical and literary discourse, but also future world-renowned artists, even if they were just in their earliest artistic phases at the time. that Markuš What is of additional importance for this term is connects it with the term optical art, emphasising that optico-plastic, four decades earlier, anticipates the term op art. Archipenko exhibited his works in Belgrade in April 1924, as part of the First Zenit International Exhibition of New Art at the Stanković Music School. The international importance of the Zenit magazine, as well as the effects of the Archipenko-Micić cooperation, is evidenced by the fact that soon after the publication of the monograph, Archipenko sent an invitation to Zenit to join the International Society of New Artists in New York, led by Catherine Dreyer and Wassily Wassilyevich Kandinsky and whose one of the presidents was Marcel Duchamp (Henri-Robert-Marcel Duchamp). The lavish talent of these two artists, Alexander Archipenko and Ljubomir Micić, deserves continuous and additional research, as well as new interpretations of their joint work.